Impact of the head cavity and submerged nozzle on corner vortices and pressure oscillations in a solid rocket motor with a backward-facing step - Hongbo Xu; Jie Hu; Chao Huo; Yifang He; Peijin Liu (Defence Technology, 2025)
Taking a C1x motor with a backward-facing step which can generate a typical corner vortex as a reference, a numerical methodology using large eddy simulation was established in this study. Based on this methodology, the position of the backward-facing step of the motor was computed and analyzed to determine a basic configuration. Two key geometrical parameters, the head cavity angle and submerged nozzle cavity height, were subsequently introduced. Their effects on the corner vortex motion and their interactions with the acoustic pressure downstream of the backward-facing step were analyzed. The phenomena of vortex acoustic coupling and characteristics of pressure oscillations were further explored. The results show that the maximum error between the simulations and experimental data on the dominant frequency of pressure oscillations is 5.23%, which indicates that the numerical methodology built in this study is highly accurate. When the step is located at less than 5/8 of the total length of the combustion chamber, vortex acoustic coupling occurs, which can increase the pressure oscillations in the motor. Both the vorticity and the scale of vortices in the downstream step increase when the head cavity angle is greater than 24°, which increases the amplitude of the pressure oscillation by maximum 63.0%. The submerged nozzle cavity mainly affects the vortices in the cavity itself rather than those in the downstream step. When the height of the cavity increases from 10 to 20 mm, the pressure oscillation amplitude under the main frequency increases by 39.1%. As this height continues to increase, the amplitude of pressure oscillations increases but the primary frequency decreases.